A Mouse Strain Defective in Both T Cells and NK Cells Has Enhanced Sensitivity to Tumor Induction by Plasmid DNA Expressing Both Activated H-Ras and c-Myc - Sheng-Fowler, Li; Tu, Wei; Fu, Haiqing; Murata, Haruhiko; Lanning, Lynda; Foseh, Gideon; Macauley, Juliete; Blair, Donald; Hughes, Stephen H.; Coffin, John M.; Lewis, Andrew M., Jr; Peden, Keith (PLOS ONE, 2014)
As part of safety studies to evaluate the risk of residual cellular DNA in vaccines manufactured in tumorigenic cells, we have been developing in vivo assays to detect and quantify the oncogenic activity of DNA. We generated a plasmid expressing both an activated human H-ras gene and murine c-myc gene and showed that 1 µg of this plasmid, pMSV-T24-H-ras/MSV-c-myc, was capable of inducing tumors in newborn NIH Swiss mice. However, to be able to detect the oncogenicity of dominant activated oncogenes in cellular DNA, a more sensitive system was needed. In this paper, we demonstrate that the newborn CD3 epsilon transgenic mouse, which is defective in both T-cell and NK-cell functions, can detect the oncogenic activity of 25 ng of the circular form of pMSV-T24-H-ras/MSV-c-myc. When this plasmid was inoculated as linear DNA, amounts of DNA as low as 800 pg were capable of inducing tumors. Animals were found that had multiple tumors, and these tumors were independent and likely clonal. These results demonstrate that the newborn CD3 epsilon mouse is highly sensitive for the detection of oncogenic activity of DNA. To determine whether it can detect the oncogenic activity of cellular DNA derived from four human tumor-cell lines (HeLa, A549, HT-1080, and CEM), DNA (100 µg) was inoculated into newborn CD3 epsilon mice both in the presence of 1 µg of linear pMSV-T24-H-ras/MSV-c-myc as positive control and in its absence. While tumors were induced in 100% of mice with the positive-control plasmid, no tumors were induced in mice receiving any of the tumor DNAs alone. These results demonstrate that detection of oncogenes in cellular DNA derived from four human tumor-derived cell lines in this mouse system was not possible; the results also show the importance of including a positive-control plasmid to detect inhibitory effects of the cellular DNA.